Knowledge, Attitudes, and Practice of Green Dentistry: A Scoping Review - Lia Hapsari Andayani; Abdul Gani Soulissa; Joey Danwieck (Journal of Indonesian Dental Association, 2024)
One of the things that contribute to global warming and environmental damage is medical waste from dental practice. Green Dentistry is an eco-friendly concept of dental practice. Green Dentistry is present as a solution to preserve natural resources, reducing energy use and lessen the waste produced. This study aimed to obtain an overview of knowledge, attitudes, and practice of green dentistry among dentists and dental students. This scoping review uses a literature search on the Google Scholar database guided by PRISMA. The study population was dentists and dental students. Inclusion criteria were observational studies on green dentistry published during 2018 - 2022 in English and Indonesian language. Articles were selected based on tittle, abstract and full text. Extracted data was presented in tables and summarized for an overview of evidence. From 88 articles obtained, 11 articles were included in this review. Each article contains knowledge, attitudes and practice regarding green dentistry, eco-friendly practices in dental clinic, and medical waste management. Each article uses a questionnaire with various number of domains and items. Knowledge, attitudes, and practice of dentists and dental students regarding green dentistry are still not evenly distributed. Postgraduate dentists were found to have better knowledge. Barriers that were often encountered are cost factors and lack of training or information. Knowledge regarding green dentistry concept among dentist and dental students still needs to be improved. Providing information about specific actions related to the concept of green dentistry is necessary.